What do people know? Ecosystem services, public perception and sustainable management of urban park trees in London, U.K. - Collins,C; Cook-Monie,I; Raum,S (Urban Forestry and Urban Greening, 2019)
Engagement with users and other public stakeholder groups is important when making planning and planting decisions for urban parks; it ensures the public feel involved and that decisions have longstanding support. Park trees provide an array of important ecosystem services but are threatened by pressures such as climate change, diseases and lack of management resources. It is important to ensure the public appreciate the breadth of services provided, and the challenges faced, by park trees. To evaluate the baseline public understanding of these issues, we surveyed 344 members of the public in London, U.K. parks to examine their perception of the importance of park trees and their understanding of the challenges they face. This exploratory study found that though the term ‘Ecosystem Service’ was largely unfamiliar, the public value park trees highly. Affluence and other demographic factors appear to have little influence on these perceptions, however, age and visit frequency slightly influenced the perceived importance of trees for their contribution to park aesthetics. Urbanisation and proximate human threats, especially pollution were considered by respondents the most important challenges facing park trees. Disease and climate change ranked 4th and 15th respectively, indicating that public education about the challenges facing park trees may be needed in advance of, or as part of plans for sustainable park management and plantings.